2022
DOI: 10.1088/1361-6439/ac70a6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of simulated muscle based on single chip of AlN piezoelectric micromachined ultrasonic transducer

Abstract: Most of current portable B-mode medical imaging is based on traditional ultrasonic transducers (UTs) or capacitive micromachined ultrasonic transducers (cMUTs), both of them have defects that impede satisfying performance. Piezoelectric micromachined ultrasonic transducers (pMUTs) is a promising solution for portable/wearable B-mode imaging as alternative. This work demonstrates B-mode imaging of simulated muscle with an aluminum nitride (AlN) pMUT array for application of muscle disorder diagnosis. A 23×26 pM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The transmit performance of this work demonstrates superior results compared to those presented in [28,29], primarily attributed to the larger total area. Despite having a smaller area than the [7], the utilization of ScAlN films and higher FFs in this work leads to improved transmit sensitivity. The PMUTs in [30] have good transmit performance but are lower than the transmit sensitivity of this work.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmit performance of this work demonstrates superior results compared to those presented in [28,29], primarily attributed to the larger total area. Despite having a smaller area than the [7], the utilization of ScAlN films and higher FFs in this work leads to improved transmit sensitivity. The PMUTs in [30] have good transmit performance but are lower than the transmit sensitivity of this work.…”
Section: Characterizationmentioning
confidence: 99%
“…A fetal scan was carried out with their probe connected to a smartphone. Qu et al demonstrated B-mode imaging of simulated muscle with a piezoelectric micromachined ultrasound transducer (PMUT) array for application of muscle disorder diagnosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increased interest recently in the development of flexible US transducers using high performance piezoelectric thin film materials, such as AlN, ZnO and PZT, as shown in Figure 1 b [ 19 , 27 ]. These materials could be deposited on flexible substrates, such as thin metallic foils, to prepare flexible US transducers [ 16 , 18 , 19 , 27 , 33 ], due to the inherent physical flexibility of the film or the ultrathin thickness weakening its inherent stiffness. Vincenzo et al reported a flexible US transducer, which was based on micromembranes of piezoelectric AlN embedded between two Molybdenum electrodes on a Kapton substrate [ 27 ].…”
Section: Advances In Functional Materials For Flexible Us Transducersmentioning
confidence: 99%
“…Recently, flexible US transducers with high performances in converting mechanical energy into electrical energy have attracted tremendous attention. Several groups have proposed some typical design strategies, such as attaching rigid piezoelectric material films to flexible substrates to construct flexible US transducers, directly fabricating flexible US transducers based on piezopolymers and flexible piezocomposites, embedding many rigid micromachined US transducer elements into flexible polymer substrates, and so on [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The recent boom in the development of flexible electronic technology has also laid the foundation for the fabrication of higher performance flexible US transducers, especially for flexible array US transducers.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric micromachined ultrasonic transducers (pMUTs) manufactured using micro-electro-mechanical system (MEMS) technology offer many advantages, including low cost, miniaturization, and compatibility with microelectronics, while retaining the merits of the bulk piezoelectric ultrasonic transducers 33,34 . These pMUTs have been applied in various fields, including handheld devices for medical imaging [35][36][37] , fingerprint recognition 38,39 , wireless communication 40,41 , haptic feedback 42 .…”
mentioning
confidence: 99%